2012
DOI: 10.1002/bdra.23076
|View full text |Cite
|
Sign up to set email alerts
|

Expression and mutation analyses implicate ARHGAP29 as the etiologic gene for the cleft lip with or without cleft palate locus identified by genome‐wide association on chromosome 1p22

Abstract: Background Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is a common birth defect with complex etiology reflecting the action of multiple genetic and/or environmental factors. Genome wide association studies have successfully identified five novel loci associated with NSCL/P including a locus on 1p22.1 near the ABCA4 gene. Since neither expression analysis nor mutation screening support a role for ABCA4 in NSCL/P, we investigated the adjacent gene ARHGAP29. Methods Mutation screening for ARHGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(132 citation statements)
references
References 53 publications
9
118
3
2
Order By: Relevance
“…There is also the need to functionally validate the pathogenicity or otherwise of these variants in vivo. Rare variants in ARHGAP29 (Leslie et al 2012), PAX7 and VAX1 (Butali et al 2013;Leslie et al 2015), BMP4 (Suzuki et al 2009), FOXE1 (Moreno et al 2009), MAFB , and MSX1 (Liang et al 2012) have been observed in NSOFC cases.…”
Section: Discussionmentioning
confidence: 99%
“…There is also the need to functionally validate the pathogenicity or otherwise of these variants in vivo. Rare variants in ARHGAP29 (Leslie et al 2012), PAX7 and VAX1 (Butali et al 2013;Leslie et al 2015), BMP4 (Suzuki et al 2009), FOXE1 (Moreno et al 2009), MAFB , and MSX1 (Liang et al 2012) have been observed in NSOFC cases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although both genes share a common function in regulating keratinocyte migration during wound healing, they appear to act in different pathways that converge at regulating the activity of RhoA. Specifically, Irf6 was shown to regulate Arhgap29 (Leslie et al, 2012), but Grhl3 was shown to regulate RhoGEF19 (also known as Arhgef19) (Caddy et al, 2010). Future studies will be needed to understand the complex gene regulatory network between these two transcription factors during keratinocyte migration and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA activation is also required for the formation of TGFb3-induced stress fibers and for mediating TGFb3 signaling during palatogenesis (Kaartinen et al, 2002). Additionally, we identified Arhgap29, a GEF with high affinity for RhoA, as a novel cleft candidate gene downstream of Irf6 (Leslie et al, 2012;Saras et al, 1997). Because Irf6 is required for proper palatogenesis (Ingraham et al, 2006;Knight et al, 2006) and is a downstream effector of TGFb3 (Knight et al, 2006;Xu et al, 2006), we hypothesize that Irf6 regulates the actin cytoskeleton in keratinocytes and alters cellular migration.…”
Section: Introductionmentioning
confidence: 87%
“…Although no rare variants were included in functional assays, this study identified several associated clusters of rare variants near NTN1 and NOG. As with a previous candidate gene study, this targeted sequencing study revealed four nonsense mutations within ARHGAP29 [69]. All of the regions selected from GWAS showed strong statistical signals, and one of these, 17q22 near NOG, was tested for function.…”
Section: Next-generation Sequencing Of Ofcsmentioning
confidence: 97%
“…Recently, there has been a resurgence of candidate gene resequencing studies following the genome-wide studies described above to provide evidence that the nearby genes are causal for OFCs. Briefly, these studies have provided evidence for GREM1 [68], MAFB [50], and ARHGAP29 [69] and have examined PAX7 [70], VAX1 [71], ABCA4 [50], and NOG [68]. Sanger sequencing has been the approach taken for these studies but is inefficient for large intervals and relies on a priori knowledge to select genes for sequencing.…”
Section: Next-generation Sequencing Of Ofcsmentioning
confidence: 98%